Sistem Manajemen Rantai Pasok (MRP) Produksi Penjualan Mebel Dengan Metode JIT Pada UD. Putra Sinjai - Muflih Ramadhan; Asrul Azhari Muin; Syahbuddin Syahbuddin (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The furniture industry faces challenges in managing production and distribution efficiently due to mismatches between customer demand and stock availability. UD. Putra Sinjai, as one of the furniture businesses in Gowa Regency, experiences difficulties in accurately planning production quantities and procuring raw materials. This study aims to design and implement a supply chain management (MRP) system using the Just In Time (JIT) method to improve production and sales efficiency. The research method employed is descriptive qualitative with a case study approach through observation, interviews, and documentation. The system was designed using the Agile development method with an Extreme Programming (XP) approach, which prioritizes flexibility and direct user involvement at every stage. The results show that the implementation of this system helps reduce waste, improve the accuracy of raw material management, and accelerate the production process according to consumer demand. The effectiveness measurement using the SCOR (Supply Chain Operations Reference) method with the indicators of plan, source, make, deliver, and return shows improved operational performance at UD. Putra Sinjai. With this system, the company is able to manage inventory in real-time, schedule production based on orders, and provide transparent information to customers. This study makes a tangible contribution by integrating information technology with a JIT-based furniture production management system, while simultaneously enhancing customer satisfaction and overall business competitiveness.